A Weighted Engineering Geological Framework for Evaluating Post-Mining Land Reclamation Suitability Based on Slope, Material Properties, and Drainage - Kasmira Kasmira; Muh Arif Idhan (Ali Institute of Research and Publication, 2026)
Post-mining reclamation often underperforms when land is considered ready for revegetation without prior engineering geological screening. This study develops and demonstrates a weighted engineering geological framework for evaluating reclamation suitability based on slope condition, material properties, and drainage performance. A descriptive-evaluative design was used by combining land-unit delineation, field observation parameters, basic geotechnical indicators, drainage appraisal, and weighted scoring. To transparently demonstrate the analytical model, simulated but technically plausible data were assigned to four engineering geological zones. The model weights slope at 40%, material properties at 35%, and drainage at 25%. The resulting suitability scores classify Zone A as very suitable (87.2), Zone B as moderately suitable (72.6), Zone C as conditionally suitable (56.9), and Zone D as unsuitable (41.6). The novelty of the study lies in operationalizing slope, material, and drainage variables into a transparent zone-based suitability score, and in positioning engineering geology as the first diagnostic layer of reclamation planning rather than a post-planting correction. The framework helps identify dominant limiting factors and supports staged interventions such as regrading, drainage rehabilitation, material improvement, and phased revegetation. The model is suitable as a pre-screening tool and should be calibrated with site-specific field data in future applications.